Nanofluid cooling of 18650 lithium-ion batteries through wavy channel tube - Kanani, Nufus; Fatwa, Muhammad Ilham; Yusuf, Yusvardi; Pinem, Mekro Permana; Wahyudi, Hadi; Satria, Dhimas; Sukamto, Dwinanto; Purwamargapratala, Yustinus (Universitas Sultan Ageng Tirtayasa, 2024)
The electric vehicle (EV) industries have grown; in 2023 EV sales increased by more than 30% compared to 2022. The central issue of this industry is the battery because of the cost and environmental problems. This makes efficient battery operation and condition imperative. The electric vehicle lithium-ion batteries are highly temperature-dependent for optimal performance and longevity. A cooling system is needed to maintain the temperature of the lithium-ion battery within the optimal temperature range. This study proposes nanofluid cooling based on Cellulose Nanocrystals (CNC) inside the wavy channel tube. Other fluid cooling, such as air and water, are compared. Three-dimensional (3D) transient simulation is performed by varying the cooling fluid and mass flow rate. On the other hand, experiments were conducted to validate the simulation's conformity to the battery module's temperature. The performance of the cooling fluid inside the wavy channel effectively keeps the battery heat dissipation and temperature uniformity. The nanofluid can maintain the temperature of the battery module at its optimal temperature (below 40°C), even with the lowest flow rate (5×10-4 kg/s).